Occupational inhalation exposures to nanoparticles at six Singapore printing centers - Setyawati, Magdiel Inggrid (2021)
Laser printers emit high levels of nanoparticles (PM0.1) during operation. Although it is well established that toners contain multiple engineered nanomaterials (ENMs), little is known about inhalation exposures to these nanoparticles and work practices in printing centers. In this report, we present a comprehensive inhalation exposure assessment of indoor microenvironments at six commercial printing centers in Singapore, the first such assessment outside of the United States, using real-time personal and stationary monitors, time-integrated instrumentation, and multiple analytical methods. Extensive presence of ENMs, including titanium dioxide, iron oxide, and silica, was detected in toners and in airborne particles collected from all six centers studied. We document high transient exposures to emitted nanoparticles (peaks of ∼500 000 particles/cm3, lung-deposited surface area of up to 220 μm2/cm3, and PM0.1 up to 16 μg/m3) with complex PM0.1 chemistry that included 40-60 wt % organic carbon, 10-15 wt % elemental carbon, and 14 wt % trace elements. We also record 271.6-474.9 pmol/mg of Environmental Protection Agency-priority polycyclic aromatic hydrocarbons. These findings highlight the potentially high occupational inhalation exposures to nanoparticles with complex compositions resulting from widespread usage of nano-enabled toners in the printing industry, as well as inadequate ENM-specific exposure control measures in these settings.